Hubungan Durasi Penggunaan Gadget Terhadap Gangguan Mental Emosional Anak Usia Sekolah Kelas 4 Dan 5 Di SDN Sarakan 3 Tahun 2025 - Ziliwu, Sandra; Pratiwi, Ayu (Universitas Yatsi Madani, 2025)
serious concern in the fields of mental health and education. Children exposed to prolonged gadget use tend to experience emotional disturbances such as irritability, social withdrawal, and sleep disorders. Research Objective: This study aims to examine the relationship between gadget usage duration and emotional mental health among grade 4 and 5 students at SDN Sarakan 3. Research Method: A descriptive quantitative approach with a cross-sectional design was employed. A total of 100 respondents were selected using purposive sampling. The instruments used were a gadget usage duration questionnaire and the Strengths and Difficulties Questionnaire (SDQ). Research Results: Bivariate analysis using the Spearman Rank test showed a significant relationship between gadget usage duration and child development (p-value = 0.000). Children who used gadgets for less than 2 hours per day showed good emotional development (94.4%), while those who used gadgets for more than 3 hours tended to fall into the moderate category (68.2%). Conclusion: Gadget usage duration affects emotional mental health in children. Time limitation and content supervision are essential to support optimal child development.